OUTCOMES OF DEVELOPING A LINE OFFICIAL ACCOUNT USING DESIGN THINKING FOR PHARMACEUTICAL CARE IN CANCER PATIENTS AT LAMPANG HOSPITAL - Bupphachareonsuk, Pavit; Kitikannakorn, Nantawarn; Prakongyot, Chanin; Sirichanchuen, Buntitabhon (Thai Bulletin of Pharmaceutical Sciences, 2025)
Cancer patients receiving chemotherapy may experience adverse effects that impact their quality of life. This study utilized information technology through a verified LINE application account, applying a design-thinking approach to enhance the role of pharmacists in providing education and monitoring pharmaceutical care. Thus, the objective of this study was to evaluate the effectiveness of the development of the Oncology LPH LINE official account. This development study was conducted in three phases: 1) gathering requirements and developing the initial application, 2) testing and refining based on satisfaction surveys (full score of 5) and System Usability Scale (SUS) questionnaires (full score of 100), and 3) monitoring the outcomes of pharmaceutical care delivery. The results showed the overall satisfaction from the sample group with the final version of the LINE official account, Oncology LPH version 3, was the highest, with an average satisfaction score of 4.7 ± 0.4. The SUS score was 90.7. The most frequently accessed Rich Menu among participants was the educational information about adverse effects, with a total of 897 visits (67.6%). The most common reason participants contacted pharmacists was for dietary inquiries, accounting for 60 instances (29.1%). Regarding the assessment of adverse events from pharmaceutical care based on CTCAE version 5.0, most patients experienced mild symptoms (grades 1–2), accounting for 112 individuals (93.3%). The most observed symptom was peripheral numbness in the hands and feet (70.0%). In summary, the Oncology LPH LINE official account, when combined with pharmacist support, demonstrates strong potential in enhancing pharmaceutical care for cancer patients by improving knowledge, fostering patient engagement, and facilitating the monitoring and management of adverse effects.